PENGARUH INSENTIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT (BPR) PIJER PODI KEKELENGEN KANTOR CABANG MEDAN - Suriani, Suriani; Aprinawati, Aprinawati (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2015)
This study aims to determine the effect of Incentives and Discipline on Employee Performance at PT. Bank Perkreditan Rakyat (BPR) Pijer Podi Kekelenegen Kantor Cabang Medan. The research was conducted on PT. Bank Perkreditan Rakyat (BPR) Pijer Podi Kekelenegen Kantor Cabang Medan with a population of as many as 40 people with using total sampling. Data collection techniques used were through questionnaires (questionnaire) that is by distributing questionnaires to a sample (respondents) and collect them again. The data analysis technique used is the Multiple Linear Regression. Before the data were regressed in the first test of association between the independent variable data to test for normality, multicollinearity, and heterocedasticity. To determine the contribution of factor incentives and discipline to employee performance used formula coefficient of determination (R2). The result showed obtained that by the regression equation Y = 6,505 + 0,532 X1 + 0,247 X2+ e. And showed that simultaneous incentives and discipline on employee performance at PT. Bank Perkreditan Rakyat (BPR) Pijer Podi Kekelenegen Kantor Cabang Medan, where the value of F count = 15,215 > F table = 3,24 with level of significant (α) 0,000 < 0,05. Coefficient of determination (adjusted R square) of 0,451 means that the influence of incentives and discipline on employee performance at PT. Bank Perkreditan Rakyat (BPR) Pijer Podi Kekelenegen Kantor Cabang Medan 45,1% and the remining 54,9% is influenced by other variables outside of research. Conclusions from the research that there is a positive and significant effect of incentives and discipline on employee performance at PT. Bank Perkreditan Rakyat (BPR) Pijer Podi Kekelenegen Kantor Cabang Medan. Keywords: Incentives, Discipline, Employee Performance